2019
DOI: 10.3390/coatings9110755
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ceramics Coatings Processed by Sol-Gel for Cutting Tools

Abstract: In order to obtain better cutting tool performance, the coatings appear as an alternative in the machining process. The goal of the coating is to improve tribological conditions in the chip-tool and tool-workpiece interfaces. On the other hand, the use of coated tools decreases the wear of the tools. This study discusses the ceramic coatings characterization deposited in WC tools. The Al2O3 and TiO2 films present properties such as thermal stability, chemical inertia, high hardness, and good mechanical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Rezende et.al. [15 ] examined the characterisation of ceramic coatings applied to WC tools. The films made of Al2O3 and TiO2 have qualities including high hardness, chemical resistance, thermal stability, and good mechanical properties.…”
Section: Al203/tio2mentioning
confidence: 99%
“…Rezende et.al. [15 ] examined the characterisation of ceramic coatings applied to WC tools. The films made of Al2O3 and TiO2 have qualities including high hardness, chemical resistance, thermal stability, and good mechanical properties.…”
Section: Al203/tio2mentioning
confidence: 99%
“…The results revealed the rise of scratch resistance with an increase in annealing temperature (in the range 500-700 • C) from 0.37 to 0.47 N and from 0.38 to 0.57 N in the case of a non-fluorinated and a fluorinated hydroxyapatite, respectively. Rezende et al [62] reported that from the scratch test curves, the coating failure starts for a load of 25N for a sol-gel-derived Al 2 O 3 coating on WC tools. Mohseni et al [23] in the review paper on the adhesion of HAp coating to Ti alloy, summarized the adhesion strength values of HAp coatings on Ti-6Al-4V coated using various techniques.…”
Section: Scratch Adhesionmentioning
confidence: 99%
“…Although it is recommended in the literature that the wear performance can be improved by methods such as alloying addition, this causes a decrease in the ductility and formability of the roller material as a result of changes in the internal structure of the material (Alhussein et al, 2014;Kim et al, 2008). Recently, it has become possible to prevent such problems with various coating technologies (Luo et al, 2015;Méndez-Medrano et al, 2018;Jiang et al, 2018;Rezende et al, 2019;El Azhari et al, 2020;Yuan et al, 2021;Ling et al, 2022).…”
Section: Introductionmentioning
confidence: 99%